Lithium‐Ion‐Based Conjugated Polyelectrolyte as an Interface Material for Efficient and Stable Non‐Fullerene Organic Solar Cells. Issue 7 (27th February 2019) - Li, Junli; Liu, Jikang; Liu, Xiangfu; Wang, Rongwen; Zhang, Jian; Tu, Guoli
Abstract: An eco‐friendly n‐type water/alcohol‐soluble conjugated polyelectrolyte PFEO SO3 Li was synthesized and applied as a cathode interfacial layer in organic solar cells. The π‐delocalized polyfluorene backbone has an intimate connection with the hydrophobic active layer, and the side chain with lithium ion may move toward the ZnO layer through the self‐assembly property of conjugated polyelectrolytes. UV photoelectron spectroscopy indicated that modification with PFEO SO3 Li dramatically lowers the work function of indium‐doped tin oxide (ITO)/ZnO and may form strong interfacial dipoles between ZnO and the active layer. Meanwhile, introduction of lithium ions as spectator cations may contribute to reduction of the intrinsic surface defects of ZnO. The green emission in the photoluminescence spectrum of ZnO disappeared after modification with PFEO SO3 Li. In addition, the roughness of ZnO barely changed after coating with PFEO SO3 Li, and the surface became more hydrophobic, which demonstrates that the thin conjugated polyelectrolyte layer exhibits good adhesion with both ZnO and the active layer. These phenomena indicate that the introduction of PFEO SO3 Li makes ITO/ZnO an efficient cathode. As a result, inverted organic solar cell devices with ZnO/PFEO SO3 Li double‐interlayers exhibit high efficiencies of 11.7 and 10.6 % for PBDB‐T:IT‐M and PBDB‐T:ITIC blend systems, respectively. Abstract : Go‐between : An interfacial layer of water/alcohol‐soluble lithium‐ion‐based conjugated polyelectrolyte PFEO SO3 Li between the ZnO electron‐transport layer (ETL) and the active layer leads to enhanced device performance of non‐fullerene organic solar cells by lowering the work function and improving the ETL/active layer connection.